Maritime Cybersecurity - Bauk, Sanja; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This book highlights the importance of cybersecurity in the maritime domain, including the human and societal aspects of both cyber-crime and cyber-defense. The authors present mechanisms for early detection and prevention of cyber-attacks, as well as security protocols based on testbed nautical simulator experiments, machine learning algorithms and artificial intelligence applications. This collection of research articles addresses the ethical, societal and technical aspects of maritime cybersecurity and offers solutions to mitigate the threat of cyber-attacks. The book is designed to help both researchers and stakeholders across the maritime ecosystem, including shipping and port logistics. Research findings are presented in the following areas: human factors in maritime cyber security, cyber security awareness and skills of seafarers, vulnerabilities in electronic maritime navigation on manned and unmanned vessels, internal and external attack vectors on bridge and propulsion systems, cyber security threats and countermeasures in seaports. The book serves as a handbook for those professionally involved in or interested in cybersecurity of IT and OT systems. This book is open access, which means that you have free and unlimited access. Enriched with solutions in the ethical, regulatory, and technical levels of maritime cybersecurity; Presents considerations of cybersecurity defense techniques supported by analyses carried out on a nautical simulator; Emphasizes the importance of protection against cyber-attacks at operational, tactical, and strategic levels.
Introduction -- The future of cybersecurity at sea: Human vs. human, or AI vs. AI -- Human factors in maritime cybersecurity -- Human factor and culture in maritime cybersecurity -- Rethinking seafarer training for the digital age -- Ports of Tallinn and Koper comparative analysis including cybersecurity -- Simulating cyberattacks on autonomous sea surface vessel$1 (Bs rudder controller -- A scope review of secure broadcasting protocols for the automated identification system -- Using incremental inductive logic programming for learning spoofing attacks on maritime automated identification system data -- A concept of integrating an open-source intrusion detection system into marine vehicles -- Integrating artificial neural networks with inertial navigation systems for resilience against GPS cyber-attacks -- Machine learning cybersecurity risk valuation in autonomous surface vessels -- Automatic identification system intrusion detection using federated leering approach -- Conclusion.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Telecommunication; Transportation engineering; Traffic engineering; Law of the sea; International law; Aeronautics -- Law and legislation; Communications Engineering, Networks; Transportation Technology and Traffic Engineering; Law of the Sea, Air and Outer Space